A rare case of extrapelvic endometriosis in the right sciatic notch - Gregory Liller, DO; Sahejmeet Guraya, MD; Nathan Katragadda, BA; Vijaya Kosaraju, MD; Richard Barger, MD; Peter Young, MD; Patrick Getty, MD; Navid Faraji, MD (Radiology Case Reports)
Endometriosis is described as the proliferation of endometrial tissue outside of the uterus. This most frequently occurs within the pelvis and is a common cause of chronic pelvic pain in women of reproductive age. Rarely, endometriosis can manifest outside of the pelvis and can uncommonly involve the musculoskeletal and peripheral nervous systems. Extrapelvic endometriosis is a difficult radiologic diagnosis due to its rarity and varied magnetic resonance imaging (MRI) appearance. Diagnosis of extrapelvic endometriosis is most frequently made with biopsy and most cases within the literature are treated with surgical resection. Of the cases that were treated medically, there is a paucity of available follow-up imaging to characterize the natural history and treatment response of this entity.We present a case of extrapelvic endometriosis involving the right sciatic notch, in a 26 year old female who presented with cyclic hip pain and lumbosacral plexopathy. Initial MRI findings were nonspecific, and diagnosis was made via image guided biopsy. The patient underwent medical treatment with a gonadotropin-release hormone agonist and oral contraceptives, with close imaging follow-up including a 6-month post-treatment MRI.